2005
DOI: 10.1256/qj.04.129
|View full text |Cite
|
Sign up to set email alerts
|

Neutral turbulent flow over forested hills

Abstract: SUMMARYNumerical simulations of neutral, turbulent flow over periodic forested hills are carried out using a firstorder turbulence closure scheme. The forest is represented by the inclusion in the model of a canopy near the surface where additional drag is exerted on the flow as a result of the trees. Simulations with a more traditional roughness-length parametrization of the surface, which does not explicitly model the flow within the forest, are also carried out for comparison. Comparison of simulations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(135 citation statements)
references
References 29 publications
10
124
1
Order By: Relevance
“…The Finnigan and Belcher (2004) group of models (Ross and Vosper 2005;Ross, 2011;Finnigan 2010, 2013) for canopy flow in complex terrain utilise this approach. While the concept of an eddy diffusivity dates back to Boussinesq (1877), a physical model for K awaited the introduction of mixing length closures by Prandtl (1925) (based on momentum) and Taylor (1932) (based on vorticity).…”
Section: Mixing Length Closures For Simple and Complex Canopy Flowsmentioning
confidence: 99%
“…The Finnigan and Belcher (2004) group of models (Ross and Vosper 2005;Ross, 2011;Finnigan 2010, 2013) for canopy flow in complex terrain utilise this approach. While the concept of an eddy diffusivity dates back to Boussinesq (1877), a physical model for K awaited the introduction of mixing length closures by Prandtl (1925) (based on momentum) and Taylor (1932) (based on vorticity).…”
Section: Mixing Length Closures For Simple and Complex Canopy Flowsmentioning
confidence: 99%
“…There are many challenges to face when pursuing this goal. First, the mixing-length theory and K theory that are widely used as closure approaches to momentum equations (Wilson et al, 1998;Pinard and Wilson, 2001;Ross and Vosper, 2005;Katul et al, 2006) have been shown to have questionable validity within a forest canopy layer both theoretically (Yi, 2008) and observationally (Denmead and Bradley, 1985). Second, the analytical model (Finnigan and Belcher, 2004) is limited to neutral condition and hills of gentle slope.…”
Section: Xu Et Al: Stably Stratified Canopy Flow In Complex Terrainmentioning
confidence: 99%
“…The analytical model is developed based on the linearized perturbation theory for the flow over a rough hill (Jackson and Hunt, 1975), which assumes that the mean flow perturbations caused by the hill are small in comparison to the upwind flow. Poggi and Katul (2007b) and Ross and Vosper (2005) have shown that the analytical model fails to model the flow pattern on dense canopies on narrow hills. Third, even though turbulence closure models and large eddy simulation models have been used to simulate flow within and above the canopy in numerous published studies, most numerically reproduced canopy flow is confined to idealized cases: either neutral (Ross and Vosper, 2005;Dupont et al, 2008;Ross, 2008) or weakly unstable (Wang, 2010) atmospheric conditions, or flat terrain with a homogeneous and extensive canopy (Huang et al, 2009;Dupont et al, 2010).…”
Section: Xu Et Al: Stably Stratified Canopy Flow In Complex Terrainmentioning
confidence: 99%
“…Previous research has focused on many aspects of idealized low-level three-dimensional flow in the vicinity of isolated topography [1] [2] [3] and associated downstream wake dynamics [4] [5] [6], while studies on realistic topography have been performed in other parts of the world by several authors such as [7]- [12] among others. Regionally, while a great deal of attention has been paid to modeling wind driven ocean currents, the related problem of marine air flow over land has received considerably less attention.…”
Section: Introductionmentioning
confidence: 99%